PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN TINDAK PIDANA KEKERASAN FISIK: Studi Pada UPTD Perlindungan Perempuan dan Anak Provinsi Sumatera Utara - Hidayah, Azri Amin (Universitas Harapan Medan, 2023)
Children are the young generation who are one of the human resources who have the potential to carry forward the nation's ideals. Every country is obliged to provide adequate attention and protection to children's rights. Violence often occurs against children, which can be destructive, dangerous and frightening for children. Children who are victims of violence suffer losses, not only material, but also immaterial, such as emotional and psychological shock, which can affect the child's future life. In essence, children cannot protect themselves and various kinds of actions cause mental, physical and social harm in various areas of life and livelihood. This research is normative juridical and empirical juridical legal research as support. Normative juridical research is an approach from the perspective of statutory regulations and legal norms, and case approaches are appropriate to existing problems, while the empirical juridical approach emphasizes research aimed at gaining knowledge of statutory regulations. The legal regulation of criminal acts committed by children is regulated in Law Number 11 of 2012 concerning the Juvenile Justice System, which in principle, cases of children in conflict with the law brought in the judicial process are serious cases of a serious nature, and still prioritize the principle of best interests. for children and the punishment process is the last resort without ignoring children's rights. Apart from that, children's cases can be resolved through non-formal mechanisms using a restorative justice approach to fulfill a sense of justice for the victim so that both parties can forgive each other.